The effectiveness of micro financing towards SME growth: a study case in Cheras, Kuala Lumpur area/ Mohd Termizi Mohamed Marzuki - Mohamed Marzuki, Mohd Termizi (Faculty of Business and Management, 2010)
This research was conducted to study the relationship between the effectiveness of Micro Financing towards Small Medium Enterprise (SME) growth. The objective of this research is to identify the relationship between independent variable (Micro Financing) and dependent variable (Productivity, Income, and Subsidy). This study also was conducted to determine the effect of Micro Financing towards the productivity of SME, towards income level of SME, and lastly is to identify whether Micro Financing will helps SME to survive without subsidies from government or not. Finally, the purpose of this study is to recommend about the effective way that can be done by Amanah Ikhtiar Malaysia in helping the entrepreneur of SME. The researcher had distributed the questionnaire among 100 SME participants in Cheras, Kuala Lumpur. Increase in productivity, increase in income level, and reduce the dependencies on subsidy are the dependent variables that being selected by the researcher. After collecting the data and analyze it, the result shows that there is an association or relationship between these dependent variables and the effectiveness of Micro Financing. The finding also shows that the most important effect is the increasing in the income level and most of the respondents agree that there is strong relationship between the Micro Financing and the increasing in income level. By conducting this research also, the researcher hopes that Amanah Ikhtiar Malaysia can improve their service level in order make sure that the entrepreneurs can increase their income level.